Static and Dynamic Assessment of Intelligence in ADHD Subtypes - Fabio, Rosa Angela; Towey, Giulia Emma; Caprì, Tindara (Frontiers in Psychology, 2022)
There is a controversy about the measure of IQ in children with ADHD. Some studies report that, compared to static assessment procedures, dynamic assessment of intelligence can better measure cognitive modifiability and plasticity. The present study was designed to examine children belonging to different ADHD subtypes (inattentive, hyperactive/impulsive and combined) in terms of both static (WISC scores) and dynamic measures (Modifiability index). Thirty-four children (12 ADHD-I, 10 ADHD-H and 12 ADHD-C) were compared to a sample of 27 typically developing children. Results indicate that only the inattentive and the combined subtypes, compared with the normative sample, show lower IQ scores. The ADHD-I group presents generally low WISC scores and ADHD-H presents generally high WISC scores. Moreover, the ADHD-C group shows a low static score and a high dynamic score, indicating a wide breadth of Vygotskian children's zone of proximal development. Static and dynamic measurements together can indeed be considered a comprehensive examination of intelligence levels in ADHD children and may be essential in predicting learning capacities.